KONTRIBUSI KEPEMIMPINAN KEPALA SEKOLAH, KEDISIPLINAN GURU, DAN SARANA PRASARANA PEMBELAJARAN TERHADAP PRESTASI SEKOLAH (Studi Kasus SMP Se Kabupaten Grobogan) - SUTOMO , SUTOMO (2011)
Research purposes are (1) to know contribution of headmaster leadership, teacher performance, and learning medium to Junior High Schools performance in Grobogan District. (2) to know headmaster leadership contribution to school performance in Junior High Schools performance in Grobogan District. (3) to know teacher discipline contribution to school performance in Junior High Schools performance in Grobogan District. (4) to know learning medium and infrastructure contribution to Junior High Schools performance in Grobogan District. Research has done in Junior High Schools in Grobogan District. Research population is entire of headmaster in Junior High Schools in Grobogan District including 122 headmasters. Samples are 89 samples by using sampling technique as random sampling. Data analysis using double linear regression analysis with F test, t test, and classic assumption test (normality test, autocorrelation test, heterocedastisity, and multicolinearity test). Research results are (1) headmaster leadership, teacher discipline, and learning medium and infrastructure having positive and significant contribution to school performance in Junior High Schools in Grobogan District proved by F count 67,978 with sig value 0,000 < 0,05. (2) Headmaster leadership having positive and significant contribution to school performance in Junior High Schools in Grobogan District proved by t count 4,672 including sig 0,000 means < 0,05. (3) teacher discipline having positive and significant contribution to school performance in Junior High Schools in Grobogan District proved by t count 2,757 with sig 0,007 means < 0,005. (4) Learning medium and infrastructure having positive and significant contribution to school performance in Junior High Schools in Grobogan District with t ratio 2,711 and sig value 0,008 means < 0.05.